Family functionality and emotional intelligence in psychology students of a public university in Lima - Tello Diaz, Matias Fabio (2024)
In this research, the objective was to determine whether the association between family functionality and emotional intelligence holds true in psychology students from a public university in Lima. A self-selected non-probabilistic sampling was conducted, and the TMMS 24 (Mayer et al., 1995) and the Family Apgar (Smilkstein, 1978) were applied as measurement instruments. The results were obtained through structural equation modeling, specifically structural regression. Three models were proposed, each associating family functionality with one of the three dimensions of emotional intelligence. All three models showed adequate fit indices (CFI > .90; RMSEA < .08). Family functionality was not statistically significantly associated with emotional attention (p = .115) but is was associated with emotional clarity and emotional repair (p < .001). Additionally, family functionality explained 12.8% of emotional clarity and 25.8% of emotional repair.